2019
DOI: 10.31234/osf.io/xreu6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological bases of beauty revisited: The effect of symmetry, averageness, and sexual dimorphism on female facial attractiveness

Abstract: The theoretical factors influencing human female facial attractiveness – symmetry, averageness,and sexual dimorphism – have been extensively studied. However, through improved methodologies, recent studies have called into question their links with life history and evolutionary utility. The current study uses a range of statistical and methodological approaches to quantify how important these factors actually are in perceiving attractiveness, through the use of novel analyses and by addressing methodological w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 100 publications
3
26
2
1
Order By: Relevance
“…However, they differ from those of studies of US and Jamaican women's face preferences, which reported that women tended to prefer masculinized versions of men's faces over feminized versions (e.g., Johnston et al 2001;Penton-Voak et al 2004;Rennels et al 2008). Although some work has recently demonstrated that women's face preferences can differ according to the type of paradigm used to assess preferences (Jones and Jaeger 2019), this effect of testing paradigm is unlikely to explain this difference in preferences across studies: all of the studies described above employed similar forced-choice paradigms.…”
Section: Discussioncontrasting
confidence: 66%
“…However, they differ from those of studies of US and Jamaican women's face preferences, which reported that women tended to prefer masculinized versions of men's faces over feminized versions (e.g., Johnston et al 2001;Penton-Voak et al 2004;Rennels et al 2008). Although some work has recently demonstrated that women's face preferences can differ according to the type of paradigm used to assess preferences (Jones and Jaeger 2019), this effect of testing paradigm is unlikely to explain this difference in preferences across studies: all of the studies described above employed similar forced-choice paradigms.…”
Section: Discussioncontrasting
confidence: 66%
“…We used this paradigm in our study because it was the same as that used in the study by Glassenberg et al [8] that we were attempting to (and successfully did) replicate. However, some recent research suggests that forced-choice paradigms can produce qualitatively different patterns of results that other methods for assessing preferences for sexually dimorphism face-shape characteristics [18]. Establishing the extent to which the effects of sexual orientation on face preferences that we observed in the current study and that were also observed by Glassenberg et al [8] generalize to other methods for assessing face preferences would be an important direction for future research.…”
Section: Discussionsupporting
confidence: 51%
“…Some work suggests that findings for forced choice preferences (the type of preferences we assessed in the current study) do not necessarily generalize to studies using rating paradigms [19]. Since Valentová et al [10] used a rating paradigm, this type of paradigm-contingent difference might explain why we did not replicate the effect of partnership status that they reported.…”
Section: Plos Onementioning
confidence: 56%